2011
DOI: 10.1111/j.1365-2567.2011.03427.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the antigenicity of the NKG2D ligand H60a in tumour cells

Abstract: Summary H60a is a minor histocompatibility antigen expressed in BALB and 129/Sv but not C57BL/6 mouse strains. The majority of CD8+ T cells in C57BL/6 mice responding to BALB.B splenocytes are specific for H60a. Interestingly, H60a is expressed constitutively on tumour cells, but its nature as a tumour rejection antigen, as a parallel to its function as a transplant rejection antigen, has not been studied. In this report, we show that tumour cells that constitutively express H60a at the cell surface can be rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…H60a (minor histocompatibility antigen 60a) is an NKG2D ligand that binds to NKG2D with high affinity and activates NK cell lysis . We recently found that H60a can act as a tumour antigen in allogeneic but not syngeneic systems, hence activating H60a‐specific CD8 + T cells . As a target of both T and NK cells, H60a undergoes cancer immuno‐editing such that tumours that arise in immune‐deficient mice generally have higher levels of H60a than tumours that arise in wild‐type mice .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…H60a (minor histocompatibility antigen 60a) is an NKG2D ligand that binds to NKG2D with high affinity and activates NK cell lysis . We recently found that H60a can act as a tumour antigen in allogeneic but not syngeneic systems, hence activating H60a‐specific CD8 + T cells . As a target of both T and NK cells, H60a undergoes cancer immuno‐editing such that tumours that arise in immune‐deficient mice generally have higher levels of H60a than tumours that arise in wild‐type mice .…”
Section: Introductionmentioning
confidence: 99%
“…17 We recently found that H60a can act as a tumour antigen in allogeneic but not syngeneic systems, hence activating H60a-specific CD8 + T cells. 18 As a target of both T and NK cells, H60a undergoes cancer immuno-editing such that tumours that arise in immune-deficient mice generally have higher levels of H60a than tumours that arise in wild-type mice. 6 It is not known how tumour cells decrease their level of H60a to evade immune recognition.…”
Section: Introductionmentioning
confidence: 99%